Ethics knowledge of recent paediatric residency graduates: the role of residency ethics curricula. Issue 12 (19th October 2016) - Kesselheim, Jennifer C; Najita, Julie; Morley, Debra; Bair, Elizabeth; Joffe, Steven
Abstract : Objective: To evaluate the relationship between recently trained paediatricians' ethics knowledge and exposure to a formal ethics or professionalism curriculum during residency. Methods: We conducted a cross-sectional survey of recently trained paediatricians which included a validated 23-item instrument called the Test of Residents' Ethics Knowledge for Pediatrics. The sample included paediatricians who completed medical school in 2006–2008, whose primary specialty was paediatrics or a paediatric subspecialty, and who completed paediatric residency training in 2010–2011. This sample was stratified based on residency programme variables: presence of a formal curriculum in ethics or professionalism, programme size and American Board of Pediatrics certifying exam passage rate. Paediatricians were randomly selected from each stratum for survey participation. Results: Among the 370 responding paediatricians (55%), the mean knowledge score was 17.3 (SD 2.2) out of a possible 23. Presence of a formal curriculum in ethics and/or professionalism was not significantly associated with knowledge. Knowledge was lowest on items about parental requests for a child to undergo genetic testing (2 items, 44% and 85% incorrect), preserving patient confidentiality over email (55% incorrect), decision-making regarding life-sustaining technologies (61% incorrect), and decision-making principles such as assent and parental permission (2 items, 47% and 49% incorrect). Conclusions: This study highlights several areas in which paediatricians' knowledge may be low and that are amenable to targeted educational interventions. These findings should prompt discussion and research among ethicists and educators about how ethics and professionalism curricula can more consistently influence paediatricians' knowledge.